2020
DOI: 10.2351/1.5122751
|View full text |Cite
|
Sign up to set email alerts
|

Matrix effect impact on measuring hardness of metals bombarded by accelerated ions using laser induced breakdown spectroscopy

Abstract: For safety reasons, the need of a fast in situ technique for measuring change in surface hardness of nuclear reactor vessel walls due to ion bombardment has great importance. Material hardness measurement using laser induced breakdown spectroscopy has been demonstrated as a new promising technique. The effect of the material matrix is one of the challenges that this technique for hardness measurement may face. In this work, the plasma excitation temperature Te has been used to measure the relative hardness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…[29] It was proved that the elements' thermal properties especially the boiling point had a great influence on the excitation temperature of the titanium alloy samples than the thermal conductivity. [30] What's more, the changes in the compressive strength of concrete affected the intensity ratio between the ionic and atomic emission lines of calcium. [31] It was confirmed that LIBS is a proper tool for the characterization of NiCrBSi-WC coatings produced by the laser cladding process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[29] It was proved that the elements' thermal properties especially the boiling point had a great influence on the excitation temperature of the titanium alloy samples than the thermal conductivity. [30] What's more, the changes in the compressive strength of concrete affected the intensity ratio between the ionic and atomic emission lines of calcium. [31] It was confirmed that LIBS is a proper tool for the characterization of NiCrBSi-WC coatings produced by the laser cladding process.…”
mentioning
confidence: 99%
“…[43] Accordingly, some researchers have focused on determining the surface hardness corresponding to the matrix effect. [28,30] It was found that the emission signals could be used to correct the interferences between elements in the sample matrix. [44] To sum up, the measurements of the homogeneity and element distribution of MMC are substantial in engineering industries as the surface irregularity has a considerable impact on the quality and performance of the products such as their hardness and wear resistance.…”
mentioning
confidence: 99%
“…As well as impurity measurements, Galmed et al used LIBS to detect the change in surface hardness of reactor wall vessels for different material matrices. 195 The plasma excitation temperature was used to measure the hardness of pure titanium and titanium alloys where hardness was changed by irradiation with different doses of 1 MeV C ions. A good relationship was found between the excitation temperature and Vickers hardness, with the sample matrix strongly influencing measurements.…”
Section: Inorganic Chemicals and Materialsmentioning
confidence: 99%
“…Galmed et al observed a robust linear relationship between plasma temperature and Vickers hardness; however, the sample matrix exerted a notable influence on measurements, particularly for samples with minimal variations in hardness values. 15 The composition of the sample significantly affects LIBS hardness measurements, particularly when there is a slight variance in hardness. This is attributed to alterations in the thermal properties of the sample impacting electron temperature (Te).…”
Section: Introductionmentioning
confidence: 99%